Determination of Spiritual Motivation, Psychological Motivation, Physiological Motivation to Economic Growth through the Religious Performance of Civil Servants in the Regional Secretariat of Karimun Regency - Prasetya Nugraha, Andika; Wibisono, Chablullah; Suaduon, Jogie; Supardi; Andi, Aludin; Hazriyanto (International Journal of Psychosocial Rehabilitation, 2020)
The vision of Karimun Regency is "The realization of Karimun Regency as a center of maritime-based faith and piety economic growth." This means that in economic growth through the performance of religious officials, which has the meaning of developing regions is carried out by continuing to advance efforts to build human age, especially from morality and morality which are based on spiritual, psychological and physiological values as research variables. Population in research: this is the entire staff in the Karimun Regency regional secretariat, amounting to 328. For the number of samples in this study, which is using the Slovin method, which was obtained from 180 respondents. Data were analyzed using Structural Equation Modeling (SEM). The software used for structural analysis is the Analysis of Moment Structures (AMOS) version 23 of Arbuckle, and for descriptive research, it uses SPSS version 23. Determination of spiritual, psychological, and physiological motivation on economic growth through the religious performance of permanent employees is a significant positive, and determination of spiritual, psychological, and physiological motivation towards economic growth through the significant religious performance of temporary employees. Significant, the determination of spiritual, psychological, physiological motivation on economic growth through the performance of civil servants is not significantly positive.